AUDIT TATA KELOLA SISTEM INFORMASI PADA PT PELAYARAN BATAM SAMUDRA PADA DOMAIN PO8, AI2 DAN ME1 - Domikeos, Mahena; AMRIZAL, AMRIZAL (Computer Science and Industrial Engineering, 2020)
PT Pelayaran Batam Samudra is a company engaged in the field of shipping agents, crew formalities, and ship chandling. The problem occurs in the SAFI (Solution for Accounting Finance and Inventory) information system in the purchasing section, the list of items that have been previously inputted does not appear automatically when it will be reused so it becomes uneffective because the list of items must be re-inputted. An information system governance audit is conducted to find out at what level of maturity the system that being used in the company. The method used in this study is Framework Cobit 4.1 with 3 sub domains, PO8, AI2, and ME1. From the result of this study, the average level of PT PBS information system maturity is at 2 – Repeatable but Intuitive.